2019
DOI: 10.1007/s11136-019-02117-9
|View full text |Cite
|
Sign up to set email alerts
|

Estimating utilities/disutilities for high-risk metastatic hormone-sensitive prostate cancer (mHSPC) and treatment-related adverse events

Abstract: Purpose To capture UK societal health utility values for high-risk metastatic hormone-sensitive prostate cancer (mHSPC) and the disutility associated with treatment-related adverse events (AEs) to inform future cost–utility analyses. Methods A literature review, and patient and clinical expert interviews informed the development of health states characterising mHSPC symptoms and the impact of treatment-related AEs on health-related quality of life (HRQL). Three base hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 18 publications
0
22
0
Order By: Relevance
“…However, most of these therapies can result in severe side effects and decrease patient quality of life. 2,58 Successful PIM-targeted therapy could be used as a neoadjuvant drug prior to surgery to shrink the tumor and enable more patients to undergo nervesparing radical prostatectomy and therefore improve functional outcomes. 5 Moreover, it has been demonstrated that PIM inhibitors can enhance the efficacy of existing PCa treatments, which will be discussed further, including radiotherapy, 10 chemotherapy, 9 and androgen deprivation.…”
Section: Pim Inhibition Within the Prostate Cancer Clinical Pathwaymentioning
confidence: 99%
“…However, most of these therapies can result in severe side effects and decrease patient quality of life. 2,58 Successful PIM-targeted therapy could be used as a neoadjuvant drug prior to surgery to shrink the tumor and enable more patients to undergo nervesparing radical prostatectomy and therefore improve functional outcomes. 5 Moreover, it has been demonstrated that PIM inhibitors can enhance the efficacy of existing PCa treatments, which will be discussed further, including radiotherapy, 10 chemotherapy, 9 and androgen deprivation.…”
Section: Pim Inhibition Within the Prostate Cancer Clinical Pathwaymentioning
confidence: 99%
“…Participants were 100 members of the general public aged over 18 years, recruited by interviewers through informal networks using quota-based convenience sampling, including snowballing, to match the general public in terms of age, sex and ethnicity. The sample size was informed by samples in other published TTO studies [30][31][32][33]. Informed consent was obtained and background sociodemographic questionnaires were completed prior to interview.…”
Section: Part Iii: Time Trade-off (Tto) Valuation Of Vignettesmentioning
confidence: 99%
“…Patient vignettes were assessed by 100 participants, and caregiver vignettes were assessed separately by 100 participants. The sample sizes are similar to many other published TTO studies [ 19 22 ]; no formal sample size calculations were performed as the study did not intend to test a specific hypothesis. In response to the COVID-19 pandemic, all interviews were conducted between August and September 2020 using online video calls (Zoom/Skype).…”
Section: Methodsmentioning
confidence: 93%